Difference between revisions of "009A Sample Final 1, Problem 4"

From Math Wiki
Jump to navigation Jump to search
 
(One intermediate revision by the same user not shown)
Line 1: Line 1:
<span class="exam"> If
+
<span class="exam"> If &nbsp;<math style="vertical-align: -5px">y=\cos^{-1} (2x)</math> compute &nbsp;<math style="vertical-align: -12px">\frac{dy}{dx}</math>&nbsp; and find the equation for the tangent line at &nbsp;<math style="vertical-align: -14px">x_0=\frac{\sqrt{3}}{4}.</math>
  
::::::<math>y=x^2+\cos (\pi(x^2+1))</math>
+
<span class="exam">You may leave your answers in point-slope form.
 
 
<span class="exam">compute &thinsp;<math style="vertical-align: -12px">\frac{dy}{dx}</math>&thinsp; and find the equation for the tangent line at <math style="vertical-align: -3px">x_0=1</math>. You may leave your answers in point-slope form.
 
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
|'''1.''' What two pieces of information do you need to write the equation of a line?
+
|'''1.''' '''Chain Rule'''
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{d}{dx}(f(g(x)))=f'(g(x))g'(x)</math>
 +
|-
 +
|'''2.''' Recall
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math>\frac{d}{dx}(\cos^{-1}(x))=\frac{-1}{\sqrt{1-x^2}}</math>
::You need the slope of the line and a point on the line.
 
 
|-
 
|-
|'''2.''' What does the Chain Rule state?
+
|'''3.''' The equation of the tangent line to &nbsp;<math style="vertical-align: -5px">f(x)</math>&nbsp; at the point &nbsp;<math style="vertical-align: -5px">(a,b)</math>&nbsp; is
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -5px">y=m(x-a)+b</math>&nbsp; where &nbsp;<math style="vertical-align: -5px">m=f'(a).</math>
::For functions  <math style="vertical-align: -5px">f(x)</math>&thinsp; and <math style="vertical-align: -5px">g(x),</math>&nbsp; <math style="vertical-align: -12px">~\frac{d}{dx}(f(g(x)))=f'(g(x))g'(x).</math>
 
 
|}
 
|}
 +
  
 
'''Solution:'''
 
'''Solution:'''
Line 24: Line 25:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|First, we compute&thinsp; <math style="vertical-align: -13px">\frac{dy}{dx}.</math> We get
+
|First, we compute &nbsp;<math style="vertical-align: -13px">\frac{dy}{dx}.</math>
 +
|-
 +
|Using the Chain Rule, we get
 
|-
 
|-
 
|
 
|
::<math>\frac{dy}{dx}\,=\,2x-\sin(\pi(x^2+1))(2\pi x).</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 +
\displaystyle{\frac{dy}{dx}} & = & \displaystyle{\frac{-1}{\sqrt{1-(2x)^2}}(2x)'}\\
 +
&&\\
 +
& = & \displaystyle{\frac{-2}{\sqrt{1-4x^2}}.}
 +
\end{array}</math>
 
|}
 
|}
  
Line 35: Line 42:
 
|To find the equation of the tangent line, we first find the slope of the line.  
 
|To find the equation of the tangent line, we first find the slope of the line.  
 
|-
 
|-
|Using <math style="vertical-align: -3px">x_0=1</math>&thinsp; in the formula for &thinsp;<math style="vertical-align: -12px">\frac{dy}{dx}</math>&thinsp; from Step 1, we get
+
|Using &nbsp;<math style="vertical-align: -14px">x_0=\frac{\sqrt{3}}{4}</math>&nbsp; in the formula for &nbsp;<math style="vertical-align: -12px">\frac{dy}{dx}</math>&nbsp; from Step 1, we get
 
|-
 
|-
 
|
 
|
::<math>m=2(1)-\sin(2\pi)2\pi\,=\,2.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 +
\displaystyle{m} & = & \displaystyle{\frac{-2}{\sqrt{1-4(\frac{\sqrt{3}}{4})^2}}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{-2}{\sqrt{\frac{1}{4}}}}\\
 +
&&\\
 +
& = & \displaystyle{-4.}
 +
\end{array}</math>
 +
|}
 +
 
 +
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 +
!Step 3: &nbsp;
 
|-
 
|-
|To get a point on the line, we plug in <math style="vertical-align: -3px">x_0=1</math>&thinsp; into the equation given.  
+
|To get a point on the line, we plug in &nbsp;<math style="vertical-align: -14px">x_0=\frac{\sqrt{3}}{4}</math>&nbsp; into the equation given.  
 
|-
 
|-
|So, we have  
+
|So, we have
 
|-
 
|-
 
|
 
|
::<math style="vertical-align: -5px">y=1^2+\cos(2\pi)=2.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
|-
+
\displaystyle{y_0} & = & \displaystyle{\cos^{-1}\bigg(2\frac{\sqrt{3}}{4}\bigg)}\\
|Thus, the equation of the tangent line is
+
&&\\
 +
& = & \displaystyle{\cos^{-1}\bigg(\frac{\sqrt{3}}{2}\bigg)}\\
 +
&&\\
 +
& = & \displaystyle{\frac{\pi}{6}.}
 +
\end{array}</math>
 
|-
 
|-
|
+
|Thus, the equation of the tangent line is &nbsp; <math style="vertical-align: -14px">y=-4\bigg(x-\frac{\sqrt{3}}{4}\bigg)+\frac{\pi}{6}.</math>
::<math style="vertical-align: -5px">y=2(x-1)+2.</math>
 
 
|}
 
|}
 +
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
Line 57: Line 78:
 
|-
 
|-
 
|
 
|
:<math>\frac{dy}{dx}=2x-\sin(\pi(x^2+1))(2\pi x)</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{dy}{dx}=\frac{-2}{\sqrt{1-4x^2}}</math>
 
|-
 
|-
 
|
 
|
:<math>y=2(x-1)+2</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>y=-4\bigg(x-\frac{\sqrt{3}}{4}\bigg)+\frac{\pi}{6}</math>
 
|}
 
|}
 
[[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']]
 
[[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 08:10, 10 April 2017

If   compute    and find the equation for the tangent line at  

You may leave your answers in point-slope form.

Foundations:  
1. Chain Rule
       
2. Recall
       
3. The equation of the tangent line to    at the point    is
          where  


Solution:

Step 1:  
First, we compute  
Using the Chain Rule, we get

       

Step 2:  
To find the equation of the tangent line, we first find the slope of the line.
Using    in the formula for    from Step 1, we get

       

Step 3:  
To get a point on the line, we plug in    into the equation given.
So, we have

       

Thus, the equation of the tangent line is  


Final Answer:  

       

       

Return to Sample Exam